Reception Information System and Cash ExpenditureBusiness Rental Services - Nababan, Daniel; Oki Dewa Brata, Ignatius; Mariana, Citra; Juni Tambuati Subing, Hesty (International Journal of Psychosocial Rehabilitation, 2020)
Companies in the industry must be able to survive the conditions in the industrial market. Therefore, companies are required to be able to develop along with the development and needs of the community in the industry. The more developed the life of the community, the more developed its food needs are. The accounting information system is a series of components within the company that are used to produce data that has been processed to produce the right decision so that it can produce financial statements, which will later be used by parties who have an interest in the company. The final results of the accounting information system built are expected to be able to make the information in the financial statements more reliable in planning, decision-making, and control. The method used in this research is the descriptive method, related to decision-making and other policies. The main activity carried out by CV. RMT is providing car rental services. There are two proposed procedures designed by the author consisting of cash disbursement procedures and cash receipts. Procedures that are made are accompanied by data flow diagrams and flow charts.